GLADIATOR (GLOVE FOR DEAF TRANSLATOR): WEARABLE FLEX SENSOR GLOVE FOR BREAKING COMMUNICATION BARRIERS THROUGH SIGN LANGUAGE TRANSLATION - Tsabita Rahma Faradisa; Helfis El Basith Setiawan; Immanuel Edward Suryowidagdo; Alya Nur Diana Putri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Communication barriers experienced by deaf and speech-impaired individuals in Indonesia continue to limit social, educational, and employment opportunities. Existing sign language translation technologies are often expensive and complex, reducing their accessibility. This study introduces GLADIATOR (Glove for Deaf Translator), an Arduino-based smart glove that uses flex sensors to translate sign language gestures into text or speech in real time. The system was designed to be affordable, simple, and easily replicated for wider community use. Performance evaluation was conducted by testing each letter and predefined word through 30 repeated trials. The results achieved 90.7% recognition accuracy, demonstrating the reliability of the proposed system in recognizing the tested gestures. GLADIATOR offers a low-cost and effective assistive technology that can help bridge communication gaps between deaf and hearing individuals while promoting more inclusive communication.